(untitled) (SAARC Journal of Agriculture, 2022)
Fifteen varieties of mungbean were evaluated for resistance against major insect pests i.e., leaf folder (Cnaphalocrocis medinalis), flea beetle (Phyllotreta nigripes), thrips (Megalurothrips distalis), gram pod borer (Helicoverpa armigera) and legume pod borer (Maruca vitrata). Screening was done on the basis of incidence of insect pests from first incidence upto harvest. Statistically significant variation on recorded data was observed at different days after sowing. The lowest leaf folder population was recorded on variety BARI Mung-4 (1.08 larvae per plot) while the highest (2.05) on variety BARI Mung-6. The flea beetle population was the lowest on variety BARI Mung-4 (1.67 flea beetles per plot) while the highest (3.04) was recorded on variety BARI Mung-6. The lowest population of thrips was observed on variety BARI Mung-4 (1.43 thrips per 10 opened flowers) and the highest population (2.67) was observed on variety BINA Moog-7. The lowest gram pod borer population was observed on variety BARI Mung-4 (1.03 caterpillars per plot) while the highest gram pod borer population was observed on variety BARI Mung-6 (2.24). The lowest population of legume pod borer was observed on variety BINA Moog-4 (1.18 larvae per plot) while the highest population (2.75) was recorded on variety BARI Mung-6. Among the tested varieties, BARI Mung-4 was proven comparatively the least pest infested and highest resistant variety. On the contrary, BARI Mung- 6 showed least resistance. Rest of the varieties expressed moderately resistance to major insect pests. The results showed that none of the tested varieties was completely resistant to major insect pests. SAARC J. Agric., 19(2): 207-217 (2021)